Clinical characteristics and prognostic analysis of SMARCA4‐deficient non‐small cell lung cancer - Xiyue Liang; Xianzheng Gao; Feng Wang; Shenglei Li; Yashu Zhou; Peng Guo; Yuanyuan Meng; Taiying Lu (Cancer Medicine, 2023)
Abstract Purpose To improve the understanding of special types of tumors, we summarized and analyzed the clinicopathological features and prognostic factors of SMARCA4‐deficient non‐small cell lung cancer (SMARCA4‐dNSCLC). Methods We selected 105 patients with SMARCA4‐dNSCLC and 221 patients with SMARCA4‐intact non‐small cell lung cancer (SMARCA4‐iNSCLC) by performing immunohistochemical analysis of 1520 NSCLC samples, and we assessed the patients' clinicopathological features and survival state. Results (1) SMARCA4‐dNSCLC was significantly associated with older age, male sex, smoking history, larger invasive tumor size, higher tumor proliferation index (Ki‐67), more adrenal metastases, more lymph node metastases, and few EGFR mutations (p < 0.05). The tumors were mostly negative for thyroid transcription factor‐1 (TTF‐1), CD34, and p40 and positive for cytokeratin 7 (CK7) in immunohistochemistry (IHC). Nineteen SMARCA4‐dNSCLC patients mostly had TP53, SMARCA4, and LRP1B mutations, and 48% of them had SMARCA4 frameshift mutations. SMARCA4‐dNSCLC patients have a worse prognosis than SMARCA4‐iNSCLC patients (HR: 0.27; 95% CI: 0.17–0.45). The overall survival (OS) of patients with stage III SMARCA4‐dNSCLC was worse than that of patients with SMARCA4‐iNSCLC, and the OS of stage IV SMARCA4‐dNSCLC patients was also worse than that of SMARCA4‐iNSCLC patients (p < 0.01). (2) Multivariate regression analysis showed that sex (HR: 4.12; 95% CI: 1.03–16.39) and smoking history (HR: 2.29; 95% CI: 1.04–5.02) had significant effects on the survival time of SMARCA4‐dNSCLC patients. In SMARCA4‐dNSCLC patients without distant metastases (stage I–III), patients with stage N2 or N3 lymph node metastases (HR: 6.35; 95% CI: 1.07–37.47) had a poor prognosis. Among patients with SMARCA4‐dNSCLC who were treated and had distant metastases (stage IV), male patients and patients treated with immunotherapy combined with chemotherapy showed a longer median overall survival (mOS). Conclusion SMARCA4‐dNSCLC has unique clinicopathological features and a shorter survival prognosis than SMARCA4‐iNSCLC. The efficacy of immunotherapy combined with chemotherapy needs to be observed for longer periods.